Republic of Indonesia Financial Sector Assessment - International Monetary Fund; World Bank (World Bank, Washington, DC, 2017)
Indonesia has exhibited strong macroeconomic performance, but developmental needs remain significant. To raise the living standards of a large population dispersed over thousands of islands, Indonesia must address several key challenges, including a sizeable infrastructure gap, relatively low productivity, and rising inequality. The authorities recognize that the financial sector needs to play a central role in overcoming such challenges. The authorities have been pursuing an ambitious agenda to promote financial sector deepening and to strengthen financial oversight and crisis management. Despite substantial progress since the last FSAP, the financial sector is not yet sufficiently able to fund development needs or boost inclusive economic growth. To promote sustainable financial sector deepening and inclusion, the authorities could consider a more coordinated, cross-cutting approach by addressing root causes. To promote inclusive economic growth and strengthen financial markets, the authorities pursue a diverse policy mix which includes: expansion of the KUR credit guarantee program with an interest subsidy add-on; a deposit interest rate ceiling; requirements for non-bank financial institutions to hold debt issued by the government and state-owned enterprises; and moral suasion to lower bank lending rates. However, these measures may not prove effective in achieving sustainably higher growth and financial deepening.